2019
DOI: 10.1186/s12966-019-0844-z
|View full text |Cite
|
Sign up to set email alerts
|

Nudging to move: a scoping review of the use of choice architecture interventions to promote physical activity in the general population

Abstract: Background Nudges are used to alter lifestyles and thus curb the rise of non-communicable diseases. Physical activity is a core prevention strategy to reduce the burden of non-communicable diseases. This paper aims to (1) give an overview of the scope of interventions using choice architecture techniques to promote physical activity at the population levels and (2) identify research gaps by analysing the different approaches in terms of class and type of intervention used. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
54
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 109 publications
(216 reference statements)
2
54
0
2
Order By: Relevance
“…This systematic literature review extends the work of Forberger et al (2019) [31] and Hollands et al (2013) [14] by providing a systematic and comprehensive overview of studies that used choice architecture interventions to encourage physical activity or to discourage sedentary behavior in adults. The results of the current review suggest that prompting is a promising choice architecture technique to increase stair use over elevator or escalator use.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…This systematic literature review extends the work of Forberger et al (2019) [31] and Hollands et al (2013) [14] by providing a systematic and comprehensive overview of studies that used choice architecture interventions to encourage physical activity or to discourage sedentary behavior in adults. The results of the current review suggest that prompting is a promising choice architecture technique to increase stair use over elevator or escalator use.…”
Section: Discussionmentioning
confidence: 53%
“…Two scoping reviews have previously provided an overview of studies using choice architecture interventions to promote physical activity [14,31], though both reviews only sparsely reported on the effectiveness of the interventions on physical activity. Moreover, there is still a lack of insight regarding the extent to which choice architecture interventions can effectuate durable behavior change after removal of the intervention [15].…”
Section: Introductionmentioning
confidence: 99%
“…To promote physical activity, there is an increasing focus on using environmental cues to promote physical activity [42], such as point-of-choice prompt signs that stimulate stair use. Such environmental cues provide relevant information in the environment when the choice is considered.…”
Section: Introductionmentioning
confidence: 99%
“…The power of nudges and use of consumer insight to guide promotions and campaigns is widely recognised by successful businesses and is increasingly being used as a tool by public health professionals and policy makers. A nudge may be defined as an individual component of choice architectureput simply, a single element that alters the context surrounding a choice (Forberger et al 2019), making that choice more attractive. Choice architecture is a framing device used to alter the presentation of a choice, in order to attempt to influence the outcome of that decision (Science & Technology Select Committee 2011).…”
Section: Reformulationmentioning
confidence: 99%